Efficacy and safety of camrelizumab combined with albumin-bound paclitaxel as third- or later-line regimen in patients with advanced non-small cell lung cancer - Zhu, Jianfeng; Yu, Yanyan; Mei, Jiaqi; Chen, Shiyao; Li, Jiufei; Jiang, Sicong (Frontiers in Immunology, 2023)
Background: The clinical efficacy and safety of camrelizumab as a third- or later-line regimen in patients with advanced non-small cell lung cancer (NSCLC) have not been determined in large clinical trials. Objective: This study aimed to evaluate the clinical efficacy and safety of camrelizumab in combination with albumin-bound paclitaxel as a third- or later-line treatment for patients with advanced NSCLC. Methods: A total of 257 patients with advanced NSCLC who were histopathologically confirmed and failed in clinical second-line therapy regimens at Jiangxi Province Cancer hospital from January 2018 to December 2021 were retrospectively selected. Patients with advanced NSCLC were divided into the single treatment group (STG) of camrelizumab, and the combined treatment group (CTG) of camrelizumab in combination with albumin-bound paclitaxel according to the treatment regimen. The primary outcomes of interest were clinical efficacy[objective response rate (ORR) and disease control rate (DCR)], progression-free survival (PFS), and overall survival (OS). Survival data were analyzed using the Kaplan-Meier method, and the log-rank test was performed. Additionally, Cox proportional hazard regression was used to analyze the correlation of prognosis and baseline characteristics between subgroups, to identify the potential independent risk factors for PFS and OS. Furthermore, the occurrence of side effects was assessed according to the Common Terminology Criteria for Adverse Events (CTCAE 4.03). Results: Of the 257 patients with advanced NSCLC included in the research, 135 patients received camrelizumab, and 122 patients received camrelizumab plus albumin-bound paclitaxel. The ORR of CTG and STG was 59.84% and 50.38%, and the DCR was 77.05% and 65.93%, respectively. The median PFS in CTG was higher than that in the STG (5.27 vs. 3.57 months, P = 0.0074), and the median OS was longer (7.09 vs. 6.47 months, P < 0.01). The lines of treatment, metastases, and PD-L1 expression levels were independent risk factors for the mPFS and mOS of patients with advanced NSCLC. The occurrence of adverse events was similar between camrelizumab and camrelizumab plus albumin-bound paclitaxel groups. Conclusion: Camrelizumab combined with albumin-bound paclitaxel as the third- or later-line regimen greatly prolonged PFS and OS of advanced NSCLC patients. A prospective clinical trial is warranted.